Leisure time behaviors: Prevalence, correlates and associations with overweight in Brazilian adults. A cross-sectional analysis - Fernandes, Romulo A. [UNESP]; Christofaro, Diego G. D.; Casonato, Juliano; Costa Rosa, Clara S. [UNESP]; Costa, Felipe F.; Freitas, Ismael F. [UNESP]; Monteiro, Henrique Luiz [UNESP]; De Oliveira, Arli Ramos (Soc Médica Santiago, 2010)
Background: Television viewing (TV viewing) is an important indicator of physical inactivity. Aim: To analyze the prevalence of different leisure time behaviors and TV viewing among healthy adults and their association with overweight. Material and Methods: Cross sectional survey in which 1061 females and 925 males aged 30 years old or more, answered a self administered questionnarie about physical activity. Respondents were classified according to frequency participation in sports, walking, cycling and TV viewing. Body mass index (BMI) was derived from self reported weight and height. Results: Less than 30% of individuals participated regularly in sports and less than 15 and 5% reported a high frequency of walking and cycling, respectively. Subjects regularly engaged in sports had a lower BMI. After adjustments, low cycling frequency and high TV viewing were associated with overweight in men and women, respectively. Conclusions: The prevalence of physical inactivity during leisure time is high among Brazilian adults and associated to obesity. (Rev Med Chile 2010; 138: 29-35).

Antecedentes: Ver televisión tiene una estrecha asociación con sedentarismo. Objetivo: Evaluar las actividades de tiempo libre de adultos sanos y el hábito de ver televisión y su asociación con sobrepeso. Material y Métodos: Estudio de corte transversal en el cual 1.061 mujeres y 925 hombres de 30 años de edad y mas contestaron una encuesta auto administrada acerca de actividad física en tiempo libre. Los sujetos fueron clasificados de acuerdo a la frecuencia con que practicaban deportes, caminaban, andaban en bicicleta y veían televisión. El índice de masa corporal (IMC) se calculó utilizando el peso y talla que los sujetos informaron tener. Resultados: Menos del 30% de los individuos practicaban deportes regularmente y menos del 15 y 5% informaron caminar o andar en bicicleta frecuentemente. Los individuos que practicaban deportes en forma regular tenían un IMC menor. Después de ajusfar los datos, una baja frecuencia de ciclismo y una alta frecuencia de ver televisión, se asociaron con sobrepeso en hombres y mujeres, respectivamente. Conclusiones: Existe una asociación entre falta de actividad física recreativa y sobrepeso en este grupo de adultos.
Asociación entre actividad física en tiempo libre con sobrepeso en adultos sanos
Keywords: Brazil; Cross-sectional study; Overweight; Sports